Artificial intelligence implementation in the Peruvianpublic sector: An analytical inventory of applications (2025) - Huancapaza Hilasaca, Joel Emerson (2025)
This article presents initial mapping and a systematic analysis of 22 artificial intelligence applications implemented across 17 Peruvian state entities, documenting for the first time the operational AI ecosystem in Peruvian public administration. The study identifies a paradoxical pattern: while Peru legislates prolifically on AI matters—currently standing as the sole Latin American nation with specific AI laws enacted—existing applications lack technical documentation regarding algorithmic transparency, bias auditing, and fundamental rights impact assessment. The research reveals an instrumental and neutral approach wherein operational efficiency supersedes responsible governance. The article underscores the necessity to transition from a prescriptive innovation framework toward a more participatory paradigm, encompassing institutional reengineering grounded in public sector management best practices and inclusive stakeholder engagement mechanisms.